2022
DOI: 10.1101/2022.07.18.500564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of EnvC and the phosphoenolpyruvate:sugar phosphotransferase system in resistance to MreB disruption

Abstract: Cell wall synthesis in bacteria is determine by two protein complexes: the elongasome and divisome. The elongasome is coordinated by the actin homolog MreB while the divisome is organized by the tubulin homolog FtsZ. While these two systems must coordinate with each other to ensure that elongation and division are coregulated, this cross talk has been understudied. Using the MreB depolymerizing agent, A22, we found that multiple gene deletions result in cells exhibiting increased sensitivity to MreB depolymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
1
0
0
Order By: Relevance
“…(32). Interestingly, a recent study demonstrated that a ptsI mutation reduces the length of E. coli cells grown in LB broth, likewise suggesting a role for sugar uptake in cell division and/or elongation (39). These data seem to be in line with what we report here -both because they suggest that some glucose is available in LB broth, and because they imply a connection between sugar metabolism and cell envelope homeostasis and cell growth.…”
Section: Discussionsupporting
confidence: 91%
“…(32). Interestingly, a recent study demonstrated that a ptsI mutation reduces the length of E. coli cells grown in LB broth, likewise suggesting a role for sugar uptake in cell division and/or elongation (39). These data seem to be in line with what we report here -both because they suggest that some glucose is available in LB broth, and because they imply a connection between sugar metabolism and cell envelope homeostasis and cell growth.…”
Section: Discussionsupporting
confidence: 91%